Peoples, States and Insurgency in Africa - Ekwe-Ekwe, Herbert (Tensões Mundiais, 2018)
The author discusses the African States’ inability to provide security and basic social services to the majority of the population. He argues that the “State of Berlin” created by the European conquest is still under the growing pressure of peoples or ‘nations’ that want to become independent. The world will have to deal with an African map in constant change based on independence movements that are not Islamic in essence.